2008
DOI: 10.1002/cbic.200700608
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of a Protein Binding Partner for the Marine Natural Product Kahalalide F by Using Reverse Chemical Proteomics

Abstract: Capable chemists: Chemists are playing an ever more important role in biology through the application of small molecules to biological systems. In this paper, we combine affinity chromatography and phage display (reverse chemical proteomics), to isolate a cellular receptor for the new anticancer drug and marine natural product, kahalalide F. The results challenge biologists to uncover the significance of the interaction between the drug and its target protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 48 publications
0
24
0
1
Order By: Relevance
“…Further studies revealed hNopp140 as molecular target of doxorubicin,169 and Bcl‐2, NSC‐1, and NFX1 as targets of paclitaxel (Table 1, entry 53),170 Ca 2+ /Calmodulin as target of the curcumin derivative HBC (Table 1, entry 54),171 UQCRB in mitochondrial complex III as target protein for terpestacin (Table 1, entry 55)172 and TACC3 as novel target for bisphenol A (Table 1, entry 56) 173. Piggott and Caruso could identify the human ribosomal protein S25 as the molecular target for the anticancer drug kahalalide F (Table 1, entry 57) using three different T7 phage‐displayed human disease cDNA libraries 174. By fingerprinting the selected clones with the frequent base cutter Hin f1 many clones could be screened very quickly, thereby facilitating the analysis of a far greater number of phages without the need for sequencing.…”
Section: Approaches To Target Identificationmentioning
confidence: 99%
“…Further studies revealed hNopp140 as molecular target of doxorubicin,169 and Bcl‐2, NSC‐1, and NFX1 as targets of paclitaxel (Table 1, entry 53),170 Ca 2+ /Calmodulin as target of the curcumin derivative HBC (Table 1, entry 54),171 UQCRB in mitochondrial complex III as target protein for terpestacin (Table 1, entry 55)172 and TACC3 as novel target for bisphenol A (Table 1, entry 56) 173. Piggott and Caruso could identify the human ribosomal protein S25 as the molecular target for the anticancer drug kahalalide F (Table 1, entry 57) using three different T7 phage‐displayed human disease cDNA libraries 174. By fingerprinting the selected clones with the frequent base cutter Hin f1 many clones could be screened very quickly, thereby facilitating the analysis of a far greater number of phages without the need for sequencing.…”
Section: Approaches To Target Identificationmentioning
confidence: 99%
“…Protein-To explore the molecular mechanisms underlying inhibition of angiogenesis by terpestacin, phage display biopanning, an approach that has proven to be a powerful means to identify cellular binding proteins of bioactive small molecules, was applied to identify terpestacin binding proteins (15,19). Terpestacin was biotinylated at either the C-24 (BT1) or C-17 (BT2) position hydroxyl group to produce an affinity ligand for the isolation of its binding proteins (Fig.…”
Section: Identification Of Human Uqcrb As a Terpestacin-bindingmentioning
confidence: 99%
“…It shows antitumor activities [346] both on transformed cell lines and on tumor specimens derived from a variety of solid human tumors [347,348]. Although the molecular bases of the tumoricidal activity of Kahalalide F are not fully established, the permeabilization of the plasma membrane leading to lyses [351], alterations in lysosome morphology [352,353], and inhibition of the ErbB3 signaling pathways [354][355][356] are involved in the mechanisms of this activity. In June 2009, PharmaMar licensed kahalalide F to Medimetriks Pharmaceuticals for uses other than oncology and neurology [350].…”
Section: Dolabella Auriculariamentioning
confidence: 99%